Anti‐proliferative and anti‐malarial activities of spiroisoxazoline analogues of artemisinin. Issue 1 (10th December 2018) - Pratap, Surya; Naaz, Fatima; Reddy, Srinivas; Jha, Kunal K.; Sharma, Kalicharan; Sahal, Dinakar; Akhter, Mymoona; Nayakanti, Devanna; Kumar, Halmuthur M. S.; , Vandana; Pandey, Kailash; Shafi, Syed
Abstract: A series of spiroisoxazoline analogues of artemisinin was synthesized by employing 1, 3‐dipolar cycloaddition between various in situ generated nitrile oxides and artemisitene. All the synthesized compounds were tested for their anti‐proliferative and anti‐malarial activities. Among the compounds tested, compound11a was found to be potent against the HCT‐15 cancer cell line with IC50  = 4.04 μM when compared to 5‐fluorouracil (IC50  = 35.53 μM). DNA cell cycle analysis shows that11a was inhibiting cell proliferation at the G2/M phase. Compound11b was found to be most active against Plasmodium falciparum with IC50  = 0.1 μM and also blocked host hemoglobin hydrolysis by the falcipain‐3 receptor. It was demonstrated to have better dynamics of parasite killing efficiency than artemisinin. Molecular docking studies revealed that these compounds interacted with falcipain‐3 receptor sites. Abstract : A series of spiroisoxazoline analogues of artemisinin was synthesized and evaluated for their anti‐proliferative and anti‐malarial activities. Compound11a demonstrated anti‐proliferative activities against the human cancer cell line HCT‐15 and compound11b showed excellent anti‐plasmodial activity. Molecular docking studies of11b suggest that this class of compounds binds differently to cysteine proteases compared to the C‐10 modified analogs.